Edukasi Atasi Anemia Pada Remaja Dalam Upaya Antisipasi Stunting Bagi Generasi Bangsa - Sugiyanto, Sugiyanto; Wildaningsih, Wildaningsih (Jurnal Abdimas Jatibara, 2025)
Healthy teenagers are an investment in the nation's future. The younger generation has an important role to continue the relay of development and development of the nation. It is in the hands of teenagers that the direction of this country is determined. One of the health problems that is the government's focus is overcoming anemia in teenagers. Anemia in adolescents has a negative impact on growth, development, cognitive abilities and learning concentration, as well as increasing susceptibility to infectious diseases. Anemia can also have a big impact when these young women become mothers and give birth to children, which can put them at risk of stunting. This PkM implementation was held on Friday 6 December 2024 from 09.00 - 11.30 WIT, located in the hall of Senior High School 2 Luwu and attended by 36 participants who were students of Senior High School 2 Luwu. In this PkM, all participants took part in the activities with enthusiasm, this was proven by the large number of activity participants and the participants were actively involved in outreach activities with enthusiasm asking about stunting in discussion sessions. After providing education about the symptoms, impacts and management of anemia, the next activity was to distribute blood supplement tablets to young women. Providing blood supplement tablets (TTD) is important to prevent anemia in young women. Anemia in adolescents can be prevented by consuming Fe tablets which are taken regularly during menstruation. Providing education to young women, especially about treating anemia, is very important to carry out regularly, this is because teenagers' understanding and awareness of the problem of anemia is still very low. Adolescent girls who menstruate are required to consume nutritious food, get enough rest and consume Fe tablets to prevent anemia.